UTILIZATION OF WEB AS AKSARA JAWA LEARNING MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Sri Lestanti (Universitas Islam Balitar, 2018)
This learning media application is designed to be able to help elementary school students in learning Aksara Jawa. This application is made web-based, so it can be used by all people. The purpose of making this application is to assist with the learning of Aksara Jawa with the subject matter of the aksara carakan with pasangan, aksara wilangan, aksara swara, tuladha page, and question page. It is expected that the presence of this learning media can help increase the students' interest in learning local content subjects, namely Regional Languages (Javanese). In addition to increasing interest, can contribute to the preservation of regional culture.